Social class and cancer survival in Turin, Italy. Issue 1 (February 1997) - Rosso, S; Faggiano, F; Zanetti, R; Costa, G
Abstract : STUDY OBJECTIVE: This study aimed to investigate social differences in cancer survival in residents of Turin, Italy. DESIGN: Incident cases from the Piedmont cancer registry were linked to municipality files and 1981 census data, and followed up from 1985-92. The census provided data on education and housing tenure, which were used as indicators of social class. The case fatality ratio (CFR) was estimated through a proportional hazard model, with socioeconomic indicators as risk factors. MAIN RESULTS: Educated people of both sexes showed better survival for all malignant neoplasms together and, particularly among men, for tumours which show a better prognosis such as cancer of colon-rectum, larynx, prostate, and bladder. The relative risk of dying, compared with people who had only primary school education, decreased from 0.91 for those with middle school education to 0.67 for those who held a university degree. CONCLUSION: There were major differences in cancer survival showing a poorer outcome for those from the lower social stratum, particularly in sites for which effective treatments are available. Since is unlikely that the observed differences could be totally explained by extraneous factors, such as competing mortality, it is concluded that even in a country where the health system offers universal coverage, non-financial barriers act by creating differences in opportunities for better care.